2009
DOI: 10.1007/s10734-009-9214-0
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral students on the university–industry interface: a review of the literature

Abstract: Doctoral students are highly important in university-firm relationships, since they are significant producers of knowledge in collaborative research projects, they are an important channel for knowledge transfer between universities and firms, and are vital in network configurations between firms and universities. An increasing number of doctoral students interact with firms, but we know relatively little about the experiences of these students or how collaboration influences their training, research and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
2
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(169 citation statements)
references
References 32 publications
4
148
2
15
Order By: Relevance
“…Moreover, we asked for assistance to contact pre-and post-doctoral researchers from different scientific disciplines within each university and requested them to fill out our online questionnaire. Our survey deliberately targeted non-tenured academic staff, as they constitute an important but often overlooked channel for knowledge transfer that will shape entrepreneurial universities in the future (Bienkowska and Klofsten 2012;Thune 2009). …”
Section: Data Collection and Samplementioning
confidence: 99%
“…Moreover, we asked for assistance to contact pre-and post-doctoral researchers from different scientific disciplines within each university and requested them to fill out our online questionnaire. Our survey deliberately targeted non-tenured academic staff, as they constitute an important but often overlooked channel for knowledge transfer that will shape entrepreneurial universities in the future (Bienkowska and Klofsten 2012;Thune 2009). …”
Section: Data Collection and Samplementioning
confidence: 99%
“…In general, it has been found that industrial PhD candidates perform more than one function on the university-industry interface (Thune, 2009). Studying Swedish PhD candidates, Bienkowska and Klofsten (2012) analysed their attitudes to commercialization of research results, finding for the category of science and engineering that only a small minority had moved between university and a firm during their PhD education, whereas less than a third had no experience of external collaboration during the same period.…”
Section: The Construction Industry and University Collaborationmentioning
confidence: 99%
“…Denne endringen har skapt flere spenninger, ikke minst i forhold til selve innholdet i doktorgradsløpet og hva som er det viktigste «produktet» som kommer ut av prosessen: Er det selve kunnskapen som er blitt utviklet eller foredlet, eller er det kandidaten selv? I denne spenningen vil man også kunne finne kimen til debatter om grunnforskningens plass i doktorgraden og hvor anvendt og arbeidsrelevant en doktorgrad bør vaere (Thune 2009). …”
Section: Innledningunclassified